CORPORATE POLITICAL CONNECTION AND AUDIT QUALITY - Armadiyanti,, Putri; Iswati, Sri (Jurnal Akuntansi dan Keuangan Indonesia, 2019)
Indonesia offers attractive conditions to explore research on political connections, because Indonesia is a developing market country with a history of strong political connections in business. This study aims to investigate how the effect of the political connections held by board of commissioners and directors in the company on auditor quality and how earnings management moderate political connections and audit quality. This study used a sample of all companies from all sectors listed on the Indonesia Stock Exchange (IDX) in 2015-2017 except financial and insurance industry companies, thus a sample of 1213 firm-years was obtained. The analysis technique used is logistic regression analysis. The results revealed that companies with board of commissioners and directors who are politically connected have a positive and significant effect on auditor quality, it means that companies with political connections tend to choose industry specialist auditors as the company's external auditors. The results also revealed that earnings management does not moderate the effect of corporate political connections on audit quality. This research provides new insights about the use of political connections in the business environment especially in audit quality decisions in Indonesia.